2.5k views
5 votes
If g(x)= 3x-5 and h(x)= 2x–4 then (goh)(x)=?​

User Tiwan
by
5.5k points

1 Answer

6 votes

Answer:

(g o h)(x) = 6x - 17

General Formulas and Concepts:

Pre-Algebra

  • Equality Properties

Algebra I

  • Composite Functions

Explanation:

Step 1: Define

g(x) = 3x - 5

h(x) = 2x - 4

(g o h)(x) is g(h(x))

Step 2: Find

  1. Substitute: (g o h)(x) = 3(2x - 4) - 5
  2. Distribute 3: (g o h)(x) = 6x - 12 - 5
  3. Combine like terms: (g o h)(x) = 6x - 17

And we have our final answer!

User Kamath
by
5.3k points